Attitude towards poverty and social class rating of residents of Brgy. Mina East, Mina, Iloilo. - Tulali, Carlos Opena
Poverty has been a way of life for many Filipinos among which are small landowners and non-landowners in the countryside and the unemployed in both the urban and rural areas. Sociology books and articles have, in fact, dwelt on various analysis and interpretations of this human malady with the fervent hope to present a clear dichotomy of the problem., This study was anchored on the belief that there are certain forces responsible for people's poverty. Among the residents of Brgy. neighborhood, landownership, land utilization, and gross annual income. It is further believed that poverty has certain psychological, physiological, cultural, and social dimensions. This study was aimed at ascertaining the dynamics of poverty as influenced by certain social characteristics of the respondents. It was also aimed to determine differences in attitude towards poverty and social class rating of landowners and non-landowners. Employed in this study were the Social Status Scale (SSS) and the Dynamic Poverty Scale (DPS). There are two research instruments design to ascertain the dynamics of poverty. The SSS determines the respondents' social class while the DPS measures the attitude towards the four aspects of poverty. This descriptive study used the stratified systematic random sampling technique in the selection of sample for the study. All households in Mina East were considered as the universe of the study. Household heads were classified as landowners or non-landowners in which an equal percentage of samples from each group were selected through random sampling. A total of 32 respondents were the selected participants in this study in which 10 are landowners and 22 are non-landowners. Scores made on the research instrument were ordered and summarized using the mean, standard deviation, percentage, and the Spearmanrho. The null hypothesis were tested at the .05 level of significance for two-tailed tests, employing the chi-square and the Mann-Whitney U test. The salient findings of the study were these. -Unskilled and semi-skilled occupations ranked first and second among the respondents as an entire group but the primary source of income is salary, followed by wages and petty profits/fees. the poor among the respondents are congregated in either non-residential area or rented lot and lived in run-down houses. There are more than twice as many landowners than there are landowners among the respondents. The average landholding is less than three hectares. The percentage of poverty in this study is lower than the estimate of the Philippines' Bishop-Businessmen's Conference of 74 percent in 1985 as perceived by the people themselves. None of the "absolute poor" or those classified as lower-lower class in this study have a gross annual income of more than P37,000 per anum. As a whole group, 68.75 percent of the respondents belong to the lower class. - As an entire group , the respondents' attitude towards the psychological, physiological, cultural, and social aspects of poverty may be one of uncertainty, indifference, or resignation. - All seven indices of social characteristics measured in the Social Status Scale (SSS) have a markedly high and positive correlation with the social class rating for the entire group. Gross annual income emerged as the variable most significantly related to social class rating. The six other variables like dwelling, occupation, neighborhood, landownership, land utilization, and source of income are relatively less significantly related to social class rating because they either contribute to or are determined by annual income. - differences exist in social class rating of landowners and non-landowners. Owning a land does not contribute significantly to the landowner's income although landownership is strongly related to the social class rating of the respondents as a whole group. - The belief-systems of the respondents have contributed to a coping mechanism which tend to make poverty a condition that one has to accept and live with. On the other hand, perceived social inequalities and the failure of certain social institutions to arrive at solutions to poverty underlie the attitude of the respondents. - the same result hold, whether the respondents are landowners or non-landowners.